Промышленное применение сварки взрывом (Обзор) - Бэнкер, Дж.Г. (Автоматическая сварка, 2009)
Приведен обзор использования технологий сварки взрывом в современном производстве. Рассмотрены их возможности и недостатки по сравнению с другими технологиями сварки металлов, представлены основные области применения этого способа сварки. The explosion welding technology was developed in several facilities around the world, primarily in the 1960s. Since then the application of the technology to make explosion welded clad plates has evolved into a significant worldwide industry. The explosion cladding technology is a proven, robust, cost effective and highly versatile process for manufacturing clad plates. It is suitable for manufacture of clad of virtually any combination of commonly used industrial metals. Today explosion welded clad plates are used in a broad range of industrial applications. The technology has a clear value niche in today's industrial world.